Research progress of microglial surface receptors in perioperative neurocognitive disorders - Chun‐Chun Tang; De‐Xing Liu; Zhao‐Qiong Zhu (Ibrain)
Abstract Perioperative neurocognitive disorder (PND) is a common complication in the perioperative period, which not only prolongs the hospitalization of patients, increases the cost of treatment, but even increases the postoperative mortality of patients, bringing a heavy burden to families and society. Mechanism exploration involves anesthesia and surgery that lead to microglial activation, promote the synthesis and secretion of inflammatory factors, cause an inflammatory cascade, aggravate nerve cell damage, and lead to cognitive dysfunction. It is believed that microglia‐mediated neuroinflammatory responses play a vital role in the formation of PND. Microglia surface receptors are essential mediators for microglia to receive external stimuli, regulate microglial functional status, and carry out intercellular signal transmission. Various microglial surface receptors trigger neuroinflammation, damage neurons, and participate in the development and progression of PND by activating microglia. In this study, the roles of immunoglobulin receptors, chemokine receptors, purinergic receptors, and pattern recognition receptors in microglia surface receptors in PND were reviewed, to provide a reference for the mechanism research, prevention, and treatment of PND.